2010
DOI: 10.1002/ar.21136
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Limb Loading and Chondral Modeling During Ontogeny

Abstract: The adaptive growth response of cartilage, or chondral modeling, can result in changes in joint and limb proportions during ontogeny and ultimately contribute to the adult form. Despite Hamrick's (1999) reevaluation of the mechanisms of chondral modeling, the process of chondral modeling remains poorly studied in animal models. Here, we characterize the macro-and microanatomical responses of the femoral growth plate, articular cartilage, and bone in 15 juvenile Sus scrofa domestica subjected to different locom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 60 publications
3
26
1
Order By: Relevance
“…In this regard, a recent study found dissimilar results regarding the plasticity responses of articular and physeal cartilage to altered limb loading (Hammond et al, 2010). In particular, support for the predictions of chondral modeling theory, including increased cell proliferation and cartilage height, was observed only for the physeal cartilage.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…In this regard, a recent study found dissimilar results regarding the plasticity responses of articular and physeal cartilage to altered limb loading (Hammond et al, 2010). In particular, support for the predictions of chondral modeling theory, including increased cell proliferation and cartilage height, was observed only for the physeal cartilage.…”
Section: Introductionmentioning
confidence: 91%
“…Chondral modeling theory predicts regional or widespread thickening of cartilage, changes in cellular and extracellular cartilage composition, and differential mineralization and ossification of hyaline tissue, thereby directly influencing bony morphology through increased bone deposition. There is evidence that chondral modeling occurs at articular and physeal cartilage surfaces (Hammond et al, 2010) and it is hypothesized to occur at sites of fascial, tendinous and ligamentous insertion (Frost, 1979).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, fish reared on different diet types develop entirely different jaw morphologies (Meyer, 1987;Wainwright et al, 1991;Adams et al, 2003;Muschick et al, 2011), which adaptively affects their feeding performance on locally abundant resources (Bouton et al, 2002;Parsons and Robinson, 2007). Similarly, rabbits reared on different diets develop entirely different jaw, palate and cranial structures (Menegaz et al, 2009;Menegaz et al, 2010), whereas pigs reared in different locomotor environments differ in joint and bone structure (Hammond et al, 2010;Congdon et al, 2012). We focus on avian bills because variation in the length, depth and width of the bill has been tied to functional variation in avian foraging, both within and between species (Grant, 1979;Smith, 1987;Benkman et al, 2001;Herrel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%